Dispute Resolution Mechanism under The 2017 FIDIC Red Book - Hdaib, Amer (2019)
The disputes between the contracting parties in construction projects are unavoidable due to the nature and complexity of the construction contracts; therefore it is important to include a dispute resolution mechanism in the construction contracts, using one of the popular standard form of contracts such as FIDIC standard forms of contracts is recommended to reduce the level of disputes between the parties, these forms are continually developed to reflect the development in the construction industry, a new revision of The FIDIC Red Book was launched in 2017 which include a fundamental development in the Dispute Resolution Mechanism. This study has discussed and analysed the efficiency of the developed dispute resolution mechanism in The 2017 FIDIC Red Book since this amendment aims to make the process of resolving the disputes in construction projects faster, cheaper, and more effective. In fact, the new forms are intended to avoid disputes between the parties by providing dispute avoidance roles to the dispute board. Although the FIDIC Red Book is broadly used in the UAE, very few projects implement the FIDIC Red Book dispute resolution mechanism to resolve disputes. This study highlighted the reasons behind that and identified the improvement from the 1999 FIDIC Red Book and whether the updated mechanism in the 2017 Red Book will encourage professionals to adopt it in new construction projects. The literature review was undertaken on the claims and dispute resolution mechanism under FIDIC standard forms of contracts followed by an online survey questionnaire distributed to construction professionals at different levels to collect a considerable amount of data to complete the required data analysis on the new FIDIC Red Book and its developed dispute resolution mechanism.